Coronavirus S antigen as a marker of effective vaccination - Spyrydonov, V.G.; Melnychuk, M.D. (Reports of the National Academy of Sciences of Ukraine, 2021)
A yeast analog of the new coronavirus (SARS-CoV-2) Spike antigen, responsible for the binding to the ACE-2 cellular receptor is obtained. The identity of the yeast analog compared to the native viral one is demonstrated in indirect ELISA and Western blot analysis using commercial rabbit anti-SARS-CoV-2 S specific serum. The immunological reactivity of the yeast S antigen has been analyzed in indirect ELISA with volunteer Sera (n = 8) collected before the vaccination and on day 28 after the first vaccination. Vaccination was carried out with the Chinese Sinovac (CoronaVac) vaccine in two stages with an interval of 14 days. The results of the analysis have shown that the antibody titer on day 28 after the first vaccination is 4 times higher than before the vaccination, which confirms the seroconversion due to the use of the vaccine and indirectly serves as a marker of the effective vaccination with the formation of virus-neutralizing antibodies.